Peace and war : armed conflicts and international order, 1648-1989 - Holsti, K. J. (Cambridge : New York : Cambridge University Press, 1991)
In this book, Professor Holsti approaches the study of the origins of war and the foundations of peace from a distinct perspective. The author identifies the variety of conflict-producing issues and the attitudes of policy makers to the use of force, which have changed over the last 350 years.
Includes bibliographical references and index.
Keywords: War; World politics; Military history, Modern; International relations